The effects of homework feedback system and homework organizational patterns on the achievements of students in college algebra - Cabalonga, Jacinto L. (Animo Repository, 1990)
This research study determines the effects of three types of homework feedback system, two types of homework organizational patterns, and their interaction in the academic achievements of students in college algebra. The study made use of 210 college freshmen from six intact classes during the first semester of SY 1989-1990. Students usually performed better in their achievement test when they are exposed to homework returned with 'positive comments and grade' than the groups exposed to homework returned with 'correct solution/answers and grade' and the group exposed to homework returned with 'grade' only. Although the homework prepared via the oblique organizational pattern is more effective than the vertical organizational pattern due to the inclusion of some exploratory items, there is no definite advantage of the former over the latter. The groups exposed to homework returned with 'comment and grade' have uniformly obtained higher achievement results regardless of which organizational pattern was used. This means that there is no significant interaction between homework feedbacks and the homework organizational pattern.